Placental Weight for Gestational Age and Adverse Neonatal Outcome at Bhumibol Adulyadej Hospital - Kesinee Lonimitdee; Sinart Prommas (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To exam association between placental weight and perinatal outcome.Materials and Methods:The retrospective cohort study was performed. Data recorded from birth records were reviewed. Placental weight was divided in to three groups, abnormal and normal weight (high and low, normal) according to placenta weight percentile at 10 and 90 percentile respectively. The association to birth weight was analyzed. Result:The abnormal placental weight group was associated with increased Apgar score at 1 and 5 minute less than 7 (RR 4.0, 95% CI = 1.79-8.91 and RR 4.22, 95% CI = 1.31-13.55), NICU admission rates (RR 4.29, 95% CI = 2.42-7.59), and respiratory complication (RR 3.0, 95% CI = 1.34-6.04) when compared with the normal placental weight group. Conclusions: Abnormal placental weight was significantly associated with adverse pregnancy outcomes such as Apgar score at 1 and 5 minute less than 7, NICU admission rates and respiratory complication.